2009
DOI: 10.1520/jai101800
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Quenching and Kinetics of Wetting of Nanofluids and Vegetable Oils

Abstract: In the present work, the suitability of vegetable oil blends with mineral oil and alumina based nanofluids as quench media for industrial heat treatment was investigated. Sunflower oil, palm oil, and mineral oil were used for preparing the blends. Alumina based nanofluids of varying concentrations ranging from 0.01–4 % were used. The size of alumina particles was about 50 nm. The severity of quenching and heat transfer coefficients were estimated during quenching of copper probes. Heat transfer coefficients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Although relatively easy to perform, this method does not readily produce vitally important continuous heat transfer profiles for a quenching medium throughout the cooling process. Such data is much more readily obtained by using an inverse method to solve the heat transfer problem such as the Finite Element Methods (FEM) utilized by many workers including recent studies involving vegetable oils reported by Kobasko [10], Carvalho [12], Jagannath [13] and Ramesh [14] and others who have utilized Finite Element Methods (FEM).…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively easy to perform, this method does not readily produce vitally important continuous heat transfer profiles for a quenching medium throughout the cooling process. Such data is much more readily obtained by using an inverse method to solve the heat transfer problem such as the Finite Element Methods (FEM) utilized by many workers including recent studies involving vegetable oils reported by Kobasko [10], Carvalho [12], Jagannath [13] and Ramesh [14] and others who have utilized Finite Element Methods (FEM).…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively easy to perform, this method does not readily produce vitally important continuous heat transfer profiles for a quenching medium throughout the cooling process. Such data are much more readily obtained by using an inverse method, such as the finite element methods (FEMs) utilized by many workers and recent studies involving vegetable oils reported by Kobasko et al [9]; Carvalho et al [11]; Jagannesh and Prabhu [12]; Ramesh and Prabhu [13]; and others who have utilized FEMs, to solve the heat transfer problem.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent work, de Souza et al [10,11], Prabhu and co-workers [12,13], and Agboola et al [14] extensively characterized a wide variety of seed oils, such as corn oil, canola oil, sunflower oil, soybean oil, and others, by cooling curve analysis using small (typically ≤12.5 mm) cylindrical probes usually constructed from Inconel 600 or a stainless steel. In addition to the characterization of cooling time and cooling rates of these oils, their heat transfer properties were determined using either a simplified computational methodology [15,16] or finite element analysis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%